2019
DOI: 10.1002/hbm.24804
|View full text |Cite
|
Sign up to set email alerts
|

Functional–structural relationship in large‐scale brain networks of patients with end stage renal disease after kidney transplantation: A longitudinal study

Abstract: It is unclear how the brain network changed after kidney transplantation (KT). We explored the patterns of large‐scale complex network after KT in end‐stage renal disease (ESRD) patients with resting‐state functional MRI (rs‐fMRI) and diffusion tensor imaging (DTI). Twenty‐one ESRD patients (14 men; mean age, 31.5 ± 9.9 years) scheduled for KT and 17 age‐ and gender‐matched healthy controls (HC) (8 men; mean age, 28.9 ± 7.2 years) were enrolled in this study. Each participant underwent rs‐fMRI and DTI scans in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
(67 reference statements)
1
7
0
Order By: Relevance
“…e vascular empty signal of MRI can rule out venous thrombosis and provide a strong basis for the development of a safe surgical plan [22]. Based on the U-Net network, a separation attention residual module and a compression excitation attention module were introduced to improve the feature mining ability of multichannel information [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e vascular empty signal of MRI can rule out venous thrombosis and provide a strong basis for the development of a safe surgical plan [22]. Based on the U-Net network, a separation attention residual module and a compression excitation attention module were introduced to improve the feature mining ability of multichannel information [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The vascular empty signal of MRI can rule out venous thrombosis and provide a strong basis for the development of a safe surgical plan [ 22 ]. Based on the U-Net network, a separation attention residual module and a compression excitation attention module were introduced to improve the feature mining ability of multichannel information [ 23 , 24 ]. The proposed DRSA-U-Net network-based abdominal multimodal image synthesis algorithm can obtain synthetic images very close to the real images in terms of visual effects and image accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Honey et al [28] directly examined relationships between the two modalities and found that in many cases, despite high RSFC, the measures were unrelated, with indirect connections playing an important role in explaining RSFC. Other studies in healthy samples and populations with medical illness have used summary measures of structural-functional connectivity across the whole brain [29,30] or across neural networks (e.g., DMN, salience network (SN) and central executive networks (CEN), which comprise the triple network [31]) [32], rather than within ROI pairs comprising a network.…”
Section: Introductionmentioning
confidence: 99%
“…Honey et al [ 28 ] directly examined relationships between the two modalities and found that, in many cases, despite high RSFC, the measures were unrelated, with indirect connections playing an important role in explaining RSFC. Other studies, in both healthy samples and populations with medical illness, have used summary measures of structural-functional connectivity across the whole brain [ 29 , 30 ] or across neural networks (e.g., DMN, salience network (SN), and central executive networks (CEN), which comprise the triple network [ 31 , 32 ]), rather than within ROI pairs comprising a single network.…”
Section: Introductionmentioning
confidence: 99%